Struktura obciążeń treningowych w cyklu przed olimpijskim Londyn 2012 - zawodnika klasy MM w rzucie oszczepem = The structure of training loads in the cycle before the Olympic London 2012 - Class MM player in the javelin - Mirosław Piątek; Krzysztof Byzdra; Maria Kamrowska-Nowak; Janusz Mikołajczyk; Robert Stępniak (Kazimierz Wielki University, 2016)
Piątek Mirosław, Byzdra Krzysztof, Kamrowska-Nowak Maria, Mikołajczyk Janusz, Stępniak Robert. Struktura obciążeń treningowych w cyklu przed olimpijskim Londyn 2012 - zawodnika klasy MM w rzucie oszczepem = The structure of training loads in the cycle before the Olympic London 2012 - Class MM player in the javelin. Journal of Education, Health and Sport. 2016;6(4):71-83. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49863 http://ojs.ukw.edu.pl/index.php/johs/article/view/3449   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 10.04.2016. Accepted: 10.04.2016.     Struktura obciążeń treningowych w cyklu przed olimpijskim Londyn 2012 - zawodnika klasy MM w rzucie oszczepem The structure of training loads in the cycle before the Olympic London 2012 - Class MM player in the javelin   Mirosław Piątek1, Krzysztof Byzdra1, Maria Kamrowska-Nowak1, Janusz Mikołajczyk1, Robert Stępniak1   1AWFiS Gdańsk 2UKW Bydgoszcz   Słowa kluczowe: trening, oszczep. Key words: training, javelin.     Streszczenie: Cel pracy wypływa z potrzeb praktyki. Ukazuje makrocykl treningowy zawodnika klasy mistrzowskiej  międzynarodowej w rzucie oszczepem. Materiał i metoda Materiał badawczy stanowią zapisy zrealizowanych treningów oszczepnika kadry narodowej, uczestnika igrzysk olimpijskich w Londynie - 2012 rok. Na podstawie zapisów, które zostały zapisane w dzienniczku treningowym przeanalizowano poszczególne mezocykle i mikrocykle treningowe pod kątem zmieniających się obciążeń. Do oceny skuteczności makrocyklu rocznego posłużoną rezultaty wszystkich startów zawodnika w sezonie 2011/2012. Wnioski             Badany w pracy plan treningowej zrealizował główny cel wyznaczony na rok 2012. Rekord życiowy badanego wynosi 84,76 metra, czyli jest lepszym wynikiem niż rezultat osiągnięty przez zwycięzcę Igrzysk. Są to oczywiście spekulacje, które mogły stać się stanem faktycznym. W pracy przestawiono głównie struktury treningu. Omówiono zarówno strukturę czasową jak i rzeczowa treningu.   Abstract: The objective of the work derives from the needs of the practice. Macrocycle shows the player between the master class training in Javelin throw. Material and method the research Material constitute records carried out training of the national team Javelin thrower, a participant in the Olympic Games in London - 2012. On the basis of the records that have been recorded in the diary of the individual examined training mezocykles and microcycles currently on training for changing workloads. To assess the effectiveness of macrocycle annual used results all start in 2011/2012. Applications Tested on the job training plan made the main goal set for the year 2012. Personal record of the test is 84.76, i.e. Metro is a better result than the results achieved by the winner of the Olympic Games. There are, of course, speculating that may have become facts. At work are mainly the structure of training. Discusses both the time structure and the kind of training.